Suppression of the tapeworm order Pseudophyllidea (Platyhelminthes: Eucestoda) and the proposal of two new orders, Bothriocephalidea and Diphyllobothriidea - Kuchta, R; Scholz, T; Brabec, J; Bray, R A (International journal for parasitology, 2008)
Pseudophyllidea van Beneden in Carus, 1863, a well recognised order of tapeworms (Platyhelminthes: Eucestoda), is suppressed because it is composed of two phylogenetically unrelated groups, for which the new names Bothriocephalidea and Diphyllobothriidea are proposed. The new orders differ from each other in the following characters: (i) position of the genital pore: on the dorsal, dorso-lateral or lateral aspects and posterior to the ventral uterine pore in the Bothriocephalidea versus on the ventral aspect of segments and anterior to the uterine pore in the Diphyllobothriidea; (ii) the presence of a muscular external seminal vesicle in the Diphyllobothriidea, which is absent in the Bothriocephalidea; (iii) the presence of a uterine sac in the Bothriocephalidea, which is absent in the Diphyllobothriidea; and (iv) the spectrum of definitive hosts: mainly teleost fishes, never homoiothermic vertebrates in the Bothriocephalidea, versus tetrapods, most frequently mammals, in the Diphyllobothriidea, with species of Diphyllobothrium, Spirometra and Diplogonoporus parasitic in humans. The Diphyllobothriidea, which includes 17 genera in four families (Digramma is synonymised with Ligula), is associated with cestode groups that have a range of plesiomorphic characters (Haplobothriidea and Caryophyllidea), whereas the Bothriocephalidea, consisting of 41 genera grouped in four families, is the sister-group to the 'acetabulate' or 'tetrafossate' cestodes, which are generally regarded as having derived characters.
Keywords: Bayes Theorem; Animals; Phylogeny; Platyhelminths; Genes, Helminth; fylogeneze; Bayesova věta; ploštěnci; geny helmintů; zvířata